Cullin Deneddylation Suppresses the Necroptotic Pathway in Cardiomyocytes - Lewno, Megan T.; Cui, Taixing; Wang, Xuejun (Frontiers in Physiology, 2021)
Cardiomyocyte death in the form of apoptosis and necrosis represents a major cellular mechanism underlying cardiac pathogenesis. Recent advances in cell death research reveal that not all necrosis is accidental, but rather there are multiple forms of necrosis that are regulated. Necroptosis, the earliest identified regulated necrosis, is perhaps the most studied thus far and potential links between necroptosis and Cullin-RING ligases (CRLs), the largest family of ubiquitin E3 ligases, have been postulated. Cullin neddylation activates the catalytic dynamic of CRLs; the reverse process, Cullin deneddylation, is performed by the COP9 signalosome holocomplex (CSN) that is formed by 8 unique protein subunits, COPS1/CNS1 through COPS8/CNS8. As revealed by cardiomyocyte-restricted knockout of Cops8 (Cops8-cko) in mice, perturbation of Cullin deneddylation in cardiomyocytes impairs not only the functioning of the ubiquitin-proteasome system (UPS) but also the autophagic-lysosomal pathway (ALP). Similar cardiac abnormalities are also observed in Cops6-cko mice; and importantly, loss of the desmosome targeting of COPS6 is recently implicated as a pathogenic factor in arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C). Cops8-cko causes massive cardiomyocyte death in the form of necrosis rather than apoptosis and rapidly leads to a progressive dilated cardiomyopathy phenotype as well as drastically shortened lifespan in mice. Even a moderate down-regulation of Cullin deneddylation as seen in mice with Cops8 hypomorphism exacerbates cardiac proteotoxicity induced overexpression of misfolded proteins. More recently, it was further demonstrated that cardiomyocyte necrosis caused by Cops8-cko belongs to necroptosis and is mediated by the RIPK1-RIPK3 pathway. This article reviews these recent advances and discusses the potential links between Cullin deneddylation and the necroptotic pathways in hopes of identifying potentially new therapeutic targets for the prevention of cardiomyocyte death.